2020
DOI: 10.1016/j.amepre.2019.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Incident Prescription Opioid Use in the U.S., 2000–2015

Abstract: Introduction: Prior studies have identified associations between obesity and numerous conditions that increase risks for chronic pain. However, the impact of obesity on prescription opioid use is not well known. This study investigates the association between obesity and incidence of long-term prescription opioid use.Methods: Fifteen panels of the Medical Expenditure Panel Survey from 2000 to 2015 were pooled to generate a sample of civilian non-institutionalized adults aged 30−84 years who were prescription o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
(35 reference statements)
0
16
1
Order By: Relevance
“…21,60 While our study suggests that individuals with obesity are unlikely to be under-treated for pain, over-treatment, if it is the case, would be concerning because, in contrast to recommended preventive care, increased receipt of opioids is a risk factor for undesirable health outcomes (e.g., overdose). 67 While obesity has been implicated in increased prevalence of pain and pain medication use, 40,68 our study focuses, instead, on whether there are disparities in the treatment of pain by restricting the sample to those with back pain and adjusting for pain interference. Future work should consider of other conditions that warrant treatment with Rx pain medication and whether patients with obesity could, in fact, be overtreated for pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,60 While our study suggests that individuals with obesity are unlikely to be under-treated for pain, over-treatment, if it is the case, would be concerning because, in contrast to recommended preventive care, increased receipt of opioids is a risk factor for undesirable health outcomes (e.g., overdose). 67 While obesity has been implicated in increased prevalence of pain and pain medication use, 40,68 our study focuses, instead, on whether there are disparities in the treatment of pain by restricting the sample to those with back pain and adjusting for pain interference. Future work should consider of other conditions that warrant treatment with Rx pain medication and whether patients with obesity could, in fact, be overtreated for pain.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Recent studies have shown a positive association between obesity and opioid use in the general population, presumably due to a higher prevalence of pain among those who are obese. 39,40 The studies focus on overall use irrespective of need or conditions, which does not speak to disparities in treatment. To focus on potential treatment disparities, we restrict our sample to persons with a given source of pain (back pain) and examine whether they received a pain prescription as treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Dependent variable: parents were classified as having chronic noncancer pain (CNCP) if, during the second interview round of each survey year, they communicated one or more conditions associated with chronic pain identified through ICD-9 and Clinical Classification Codes. The selection of these codes was informed by clinical expertise as well as by other studies that have identified chronic pain associated conditions in MEPS [10][11][12] (see Supplementary Digital Content A for list of ICD-9 codes, Supplemental Digital Content 1, http://links.lww.com/MLR/C413).…”
Section: Variablesmentioning
confidence: 99%
“…Although obesity has been associated with increased prescription opioid use in the general population ( Stokes et al., 2020 ), this association is not evident in pregnant women ( Whiteman et al., 2014 ). Conversely, pregnant women with opioid use disorders are more likely to be underweight ( Nagarajan and Goodman, 2020 ).…”
Section: Maternal Opioid Usementioning
confidence: 99%